2018
DOI: 10.1123/ijsnem.2017-0237
|View full text |Cite
|
Sign up to set email alerts
|

Matcha Green Tea Drinks Enhance Fat Oxidation During Brisk Walking in Females

Abstract: 19Intake of the catechin epigallocatechin gallate and caffeine has been shown to enhance 20 exercise-induced fat oxidation. Matcha green tea powder contains catechins and caffeine and 21 is consumed as a drink. We examined the effect of Matcha green tea drinks on metabolic,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…A study by Willems et al (2018) observed an increase in exercise-induced fat oxidation by 18% following short term intake consisting of 3 cups of Matcha on the day before and one cup of Matcha on the day of testing. In the present study, the exercise-induced fat oxidation after 3-weeks intake of Matcha green tea capsules was almost double, by 35%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study by Willems et al (2018) observed an increase in exercise-induced fat oxidation by 18% following short term intake consisting of 3 cups of Matcha on the day before and one cup of Matcha on the day of testing. In the present study, the exercise-induced fat oxidation after 3-weeks intake of Matcha green tea capsules was almost double, by 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Observations from in-vivo studies in humans on the effects of Matcha are limited (e.g. Dietz et al 2017, Willems et al 2018. Dietz et al (2017) reported acute effects of Matcha green tea powder (4 grams) on specific attentional tasks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations